Multilevel Interaction in Chemical Engineering Students from University of Costa Rica - Calderón-Castro, Jenny Andrea (2016)
This research studies the effect of multilevel interaction among students of different levels from the chemical engineering career at the University of Costa Rica regarding the development and learning of skills. The groups among whom we contacted were second year graphic analysis students and fifth year control and instrumentation students. The methodology used is qualitative case study-based; instruments used were observation and data collection, students’ logbook, interviews and questionnaires geared towards the participating population. It was observed that interaction generates a better understanding of the courses’ subject matter, as well as promote the development of social skills. Given the positive results of the experience, it is recommended to create spaces for interaction not only between students, but between teachers and even at industrial level.